Risks to the public in computers and related systems. - Neumann, Peter G. (Software engineering notes.)
Edited by Peter G. Neumann (Risks Forum Moderator and Chairman of the ACM Committee on Computers and Public Policy), plus personal contributions by others, as indicated. Opinions expressed are individual rather than organizational, and all of the usual disclaimers apply. We address problems relating to software, hardware, people, and other circumstances that affect computer systems. To economize on space, we tersify most items and include pointers to items in the online Risks Forum: (R i j) denotes RISKS vol i number j. Cited RISKS items generally identify contributors and sources, together with URLs. Official RISKS archives are available at www.risks.org (which redirects to Newcastle and gets you nice html formatting and a search engine courtesy of Lindsay Marshall; http://catless.ncl.ac.uk/Risks/i.j.html gets you (R i j)) and at ftp://www.sri.com/risks.